UJI AKTIVITAS ANTIBAKTERI EKSTRAK n-HEKSAN, ETIL ASETAT DAN ETANOL KULIT BATANG KAYU EBONI (Diospyros celebica Bakh.) MENGGUNAKAN METODE DIFUSI - Ni Luh Sumitriasih; Ahmad Ridhay; Indriani (KOVALEN: Jurnal Riset Kimia, 2019)
A study was conducted on the antibacterial activity test on n-hexane, ethyl acetate, and ethanol extracts of ebony bark (Diospyros celebica Bakh.) using a diffusion method. The purpose of this research is to know the antibacterial activity of ebony bark against Staphylococcus aureus and Escherichia coli bacteria using n-hexane, ethyl acetate dan ethanol. The method of extraction used in this research was maceration method with three polarity levels of solvent. The antibacterial activity test was performed by diffusion-well test. The results showed that ethyl acetate extract gave the highest inhibition of 26.14 mm in gram-positive bacteria (Staphylococcus aureus) and ethanol extract of 25.97 mm in gram-negative bacteria (Escherichia coli). Keywords: Ebony (Diospyros celebica. Bakh), Tree Bark, Inhibitory, Antibacterial